THE EFFECT OF BRAND AWARENESS, BRAND ASSOCIATIONS, PERCEIVED QUALITY, AND CORPORATE REPUTATION ON THE CUSTOMER SATISFACTION - Susetyo, Ridha Harseno; Ayuni, Risca Fitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to examine and explain the influene of brand awareness, brand association, perceived quality,corporate reputation on customer satisfaction of converse student consumers in Brawijaya Universtiy . The research was conducted in the area of Brawijaya University. Further purposive sampling technique was used in this research with 120 respondents. The analysis tools are Multiple Linear Regression Analysis to determine the relationship between independent variable and dependent variable. The result of the study explained that there is a significant effect between brand awareness, brand association, perceived quality,corporate reputation on customer satisfaction partially. Therefore, the research result shows that corporate reputation is the dominant variable that affects customer satisfaction. Keywords: Brand Awareness, Brand Association, Perceived Quality, Corporate Reputation,Customer Satisfaction